Factors Affecting the Integrity of Financial Statements with Company Size as a Moderation Variable - Amalia, Nurhidayah Ainun; Wawo, Andi; Jannah, Raodahtul (Journal of Business Management and Economic Development, 2024)
This study aims to examine the effect of audit quality, audit committee, leverage, and independent commissioners on the integrity of financial statements in manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. This study also examines whether company size can moderate the respective relationship between audit quality, audit committee, leverage, and independent commissioners on the integrity of financial statements. This study used a quantitative approach with a comparative causal type. The population in this study is all manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. The sampling technique uses purposive sampling. The data used in this study is secondary data accessed through the IDX website. Data analysis uses multiple regression analysis for audit quality hypothesis, audit committee, leverage, and the independent commissioner as well as absolute difference value analysis for audit quality, audit committee, leverage, and independent commissioner on financial statement integrity with company size as a moderation variable. The results of this study show that the quality of audits, audit committees, leverage, and independent commissioners have a positive and significant effect on the integrity of financial statements. The moderation variable is the size of the company able to moderate the relationship between audit quality, audit committee, and leverage on the integrity of financial statements.